2017
DOI: 10.1080/09553002.2017.1393581
|View full text |Cite
|
Sign up to set email alerts
|

Nano alterations of membrane structure on both γ-irradiated and stored human erythrocytes

Abstract: Our work shows that the irradiation procedure leads to an increase in the number and size of nanovesicles along with the dose. The functionality of RBC can be affected from changes in the roughness, becoming more fragile and susceptible to breakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
0
21
1
1
Order By: Relevance
“…These bands are present in the oxygenation state of Hb. 49 In our experiment, no changes associated with oxygenation states of Hb were observed. We hypothesize that the amount of cigarettes consumed by our volunteers is not enough to make changes the capacity of the function of Hb, and as reported before, these peaks did not appear increased because the O 2 saturation of the blood is too low.…”
Section: Raman Spectroscopy Of Smokers' Rbccontrasting
confidence: 46%
See 1 more Smart Citation
“…These bands are present in the oxygenation state of Hb. 49 In our experiment, no changes associated with oxygenation states of Hb were observed. We hypothesize that the amount of cigarettes consumed by our volunteers is not enough to make changes the capacity of the function of Hb, and as reported before, these peaks did not appear increased because the O 2 saturation of the blood is too low.…”
Section: Raman Spectroscopy Of Smokers' Rbccontrasting
confidence: 46%
“…We observed an increase in the number of nano-vesicles of smokers <5 (1.73 AE 1.52), and smokers 5-9 (1.34 AE 1.30), but only smokers >10 (2.2 AE 1.65) were statistical different (p < 0.01) compared with nonsmokers (0.73 AE 0.78). The vesiculation phenomenon was previously reported in smokers by Pretorius E. et al, 20 while Acosta-Elias M. 49 and AlZahrani K. et al, 43 reported the formation of nano-vesicles provoked by gamma radiation, that induces similar conditions like oxidative stress than cigarette smoke.…”
Section: Rbc Nano-structure Analysis By Afmmentioning
confidence: 52%
“…Red blood cells radiation damage has been well demonstrated by experimental studies which also suggest that RBC irradiation may cause accelerated RBC ‘ageing’. It is likely that irradiated RBCs are more fragile than extremely old (stored for 35–42 days) but non‐irradiated RBCs, as shown in our results.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, it has been well demonstrated that irradiation of RBCs results in morphological and biochemical damage including increased fragility; in vitro haemolysis and subsequent increase in free haemoglobin, lactate dehydrogenase and potassium levels; and decreased viability of RBCs during further storage . However, there is no clinical study to show whether these ‘radiation lesions’ are associated with unfavourable clinical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…During the first week of storage, RBC lesion is characterized by the formation of micro-defects in the RBC membrane and a decrease in the membrane roughness, as assessed by atomic force microscopy ( Girasole et al, 2012 ; Pompeo et al, 2012 ; Kozlova et al, 2015 ; Acosta-Elias et al, 2017 ). For example, Kozlova et al (2015) demonstrated that by days 9 to 12 topological defects in the form of “domains” appear on the membrane surface.…”
Section: Do Any Irreversible Changes Occur In the Early Stages Of Stomentioning
confidence: 99%